Structural tax reforms and public spending efficiency - Afonso, António (2020)
We evaluate the effects of structural tax reforms on government spending efficiency in a sample of OECD economies over the period 2007-2016. After calculating input spending efficiency scores, we assess the relevance for efficiency of narrative tax changes in a panel setup. We find that: i) input efficiency scores average around 0.6-07; ii) increases in the tax rates are reflected in falling public sector efficiency; iii) such negative effect is significant for PIT and VAT; iv) controlling for endogeneity, increases in tax rates are still associated with lower public sector efficiency, mainly in PIT; v) increasing tax bases for PIT and VAT improve public sector efficiency; vi) in economic expansion periods, increasing CIT base and reducing PIT rates, positively affect public sector efficiency; ix) in recessions, efficiency improves when PIT and VAT bases increase and CIT rate increases.